Werner Deconvolution Technique for the Interpretation of Residual Aeromagnetic Anomalies of Igbeti Schist Belt; Implication for Marble Exploration - Saminu Olatunji; Warith Adewale Adebisi (Geological Agency, 2022)
DOI:10.17014/ijog.9.2.209-217Determination of the straight down range of geologic formation between geographic latitude 8.30 0N to 9 0N and longitude 3.30 0E to 4.30 0E of the Igbeti schist belt became a thing of interest due to the on-going exploration in the region. Aeromagnetic field intensity anomaly data of the bound were then acquired, separated off regional field and a corresponding residual map obtained was later used applying Werner deconvolution method filtering tool. Three magnetic profiles were selected and labelled for the interpretation on the residual anomalies. The result shows that the depth to magnetic source has a maximum value of 1,000 m toward the subsurface in all the profiles selected, indicating the shallow nature of the magnetic source in the area. Based on the structural index shown, it further reveals solutions for contact and dyke which indicates that there are boundaries which separate rocks from one another and the presence of dyke formation. The implication of identical signature from all profiles is that the marble deposit is relative uniform extending to a great depth in the area.